Persianism in antiquity - Strootman, Rolf 1968-; Versluys, Miguel John 1971-; Franz Steiner Verlag; Persianism in antiquity 2014 Istanbul (Stuttgart Franz Steiner Verlag, 2017)
The aim of this conference is to trace the origins of the concept of "Persia" in post-Achaemenid antiquity. It was in the Hellenistic and early Roman Near East that the idea of Persia fully developed. From the second century BCE, a varied cultural style developed that can best be described as "Persianism" -- the appropriation of an idealized past through the re-use or invention of imagery and concepts associated with that past
"Many of the papers in this book originate from the two-day colloquium 'Persianism in Antiquity, held at the Netherlands Institute (NIT) in Turkey, Istanbul, on 24-25 April 2014." - (Acknowledgments)
Auch als Online-Ausgabe erschienen
"Many of the papers in this book originate from the two-day colloquium 'Persianism in Antiquity', held at the Netherlands Institute (NIT) in Turkey, Istanbul, on 24-25 April 2014." (Acknowledgments)
Beiträge überwiegend auf Englisch, 1 Beitrag auf Deutsch
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Achaemenid dynasty -- 559-330 B.C -- Historiography -- Congresses; Achaemenid dynasty -- 559-330 B.C -- Influence -- Congresses; Civilization, Ancient -- Iranian influences -- Congresses; Iran -- Foreign public opinion -- Congresses; Iran -- History -- To 640 -- Historiography -- Congresses; Konferenzschrift -- 2014 -- Istanbul